Contribution to knowledge of the Trichoptera of northwestern Algeria: New species records for the Algerian fauna and taxonomic remarks for the Maghreb fauna - Bemmoussat-Dekkak, Soumya; Abdellaoui-Hassaine, Karima; Sartori, Michel; Zamora-Muñoz, Carmen (Zootaxa, 2021)
The caddisfly fauna of Algeria is far from complete. In this study, we present data from Trichoptera sampling in northwestern Algeria (Tafna and Ghazouana River basins) during 2014–2019, enhancing knowledge of this group in the country. We were able to identify 30 species and 17 genera in the study area. Among the listed taxa, five species (Hydroptila fortunata, Ecnomus deceptor, Tinodes waeneri, Limnephilus lunatus, Setodes argentipunctellus,) are new records for Algeria. An updated species checklist of Algerian Trichoptera includes 63 species. We also provide an update of the Maghreb checklist with comments on species distributions. The Maghrebian caddisfly checklist, which includes 44 Maghrebian endemic species, is still very poor in relation to that of neighboring Mediterranean geographical areas and countries, such as the Iberian Peninsula (Spain and Portugal), France, or Italy.